Plasma electrolytic oxidation of the magnesium alloy MA8 in electrolytes containing TiN nanoparticles. Issue 5 (May 2017) - Mashtalyar, D.V.; Gnedenkov, S.V.; Sinebryukhov, S.L.; Imshinetskiy, I.M.; Puz', A.V.
Abstract : The formation of protective multifunctional coatings on magnesium alloy MA8 using plasma electrolytic oxidation (PEO) in an electrolytic system containing nanosized particles of titanium nitride was investigated. Electrochemical and mechanical properties of the obtained layers were examined. It was established that microhardness of the coating with the nanoparticle concentration of 3 g l −1 increased twofold (4.2 ± 0.5 GPa), while wear resistance decreased (4.97 × 10 −6 mm 3 N −1 m −1 ), as compared to respective values for the PEO-coating formed in the electrolyte without nanoparticles (2.1 ± 0.3 GPa, 1.12 × 10 −5 mm 3 N −1 m −1 ).